Characterisation of surface layers formed on plasma-facing components in controlled fusion devices: Role of heavy ion elastic recoil detection. (December 2015) - Ström, P.; Petersson, P.; Rubel, M.; Weckmann, A.; Brezinsek, S.; Kreter, A.; Möller, S.; Rozniatowski, K.
Abstract: Wall components retrieved from the TEXTOR tokamak after tracer experiments with nitrogen-15 and molybdenum hexafluoride (MoF6 ) injection were studied to determine deposition patterns and, by this, to conclude on material migration. Toroidal limiter tiles made of carbon fibre composites and fine grain graphite were examined using time-of-flight heavy ion elastic recoil detection analysis. Molybdenum deposition patterns indicated migration based on erosion and prompt re-deposition. Nitrogen-15 was trapped together with the deposited molybdenum. Some information on the depth distribution of species in the top 400 nm layer of the limiters was obtained; however surface roughness of the samples strongly limited resolution. In the case of molybdenum, the largest concentration was found in the 100 nm outermost layer, whereas fluorine and nitrogen-15 displayed more irregular profiles. Other species, besides deuterium fuel and carbon-12, were also identified: boron-10 and boron-11 originating from boronisations, carbon-13 from earlier tracer experiments, nitrogen-14 from plasma edge cooling and metals eroded from the Inconel wall. Highlights: TEXTOR limiter samples were studied after tracer experiments. Advantages of time-of-flight heavy ion elastic recoil detection analysis were shown. Results indicate erosion and prompt re-deposition of molybdenum. Molybdenum was found in the top 100 nm layer. Light isotopes are captured during deposition of heavy elements.